Latest results on mixing and CP violation in the charm decays at the B-factories - Bhardwaj, V. (9th International Workshop on the CKM Unitarity Triangle, CKM 2016, 2016)
In this report, latest results on mixing and CP violation in the charm decays at the B-factories are presented. c Copyright owned by the author(s) under the terms of the Creative Commons
Keywords: CP violation; Charm decays; B-factories